Variations in aggregate-associated organic carbon and polyester microfibers resulting from polyester microfibers addition in a clayey soil. (March 2020) - Zhang, G.S.; Zhang, F.X.
Abstract: Organic carbon is an essential element for sustainable soil management. While the effects of microplastics on soil physical and biological properties are presenting, it remains unclear whether the organic carbon dynamics of soil are altered by increased microplastic accumulation. The objectives of this study were to evaluate the influences of different polyester microfiber (PMF 0, 0.1% and 0.3% of soil dry weight) and organic material (OM 0, 1%, 2% and 3% of soil dry weight) addition levels on soil organic carbon and to determine the PMF distribution in aggregates from a pot experiment. After 75 days of incubation under 6 wet-dry cycles, the concentrations of soil total organic carbon did not differ significantly between the PMF (9.7 ± 6.6 g kg −1 ) and control (9.7 ± 6.9 g kg −1 ) treatments. However, PMF addition significantly reduced the organic carbon concentration in the large (>2 mm) macro-aggregates compared to the control treatment (10.6 ± 4.8 g kg −1 vs. 11.7 ± 4.4 g kg −1 ), but the results were opposite in the small (2–0.25 mm)macro-aggregates (10.2 ± 4.9 g kg −1 vs. 8.4 ± 3.8 g kg −1 ). In this study, less than 30% of added PMFs were incorporated into soil aggregates. In addition, the abundance and average length of aggregate-associated PMF in the large (2210 ± 180 particles per g aggregate and 2.08 ± 0.17 mm) and small (1820 ± 150 particles per g aggregate and 1.68 ± 0.11 mm) macro-aggregates were significantly greater than those in the micro-aggregates (1010 ± 70 particles per g aggregate and 0.72 ± 0.05 mm). Our results demonstrate that the distribution of organic carbon in soil macro-aggregates is affected by PMFs addition. Thus, we propose that the behavior of microplastics inside soil aggregates should be further explored to clarify their effects on the physical protection of soil organic carbon. Graphical abstract: Image 1 Highlights: Polyester microfibers changed the concentration of macroaggregate-associated organic carbon but did not alter soil total organic carbon concentration. < 30% of added polyester microfibers is incorporated into soil aggregates. The abundance and average length of aggregate-associated polyester microfibers reduced with soil aggregate size reducing. The content of aggregate-associated polyester microfibers can be increased by organic materials addition.